PD-1Hi CAR-T cells provide superior protection against solid tumors - Sailer, Cooper J.; Hong, Yeonsun; Dahal, Ankit; Ryan, Allison T.; Mir, Sana; Gerber, Scott A.; Reagan, Patrick M.; Kim, Minsoo (Frontiers in Immunology, 2023)
Chimeric antigen receptor (CAR)-T cell therapy has emerged as a promising treatment option for several hematologic cancers. However, efforts to achieve the same level of therapeutic success in solid tumors have largely failed mainly due to CAR-T cell exhaustion and poor persistence at the tumor site. Although immunosuppression mediated by augmented programmed cell death protein-1 (PD-1) expression has been proposed to cause CAR-T cell hypofunction and limited clinical efficacy, little is known about the underlying mechanisms and immunological consequences of PD-1 expression on CAR-T cells. Here, we found that both manufactured murine and human CAR-T cell products displayed phenotypic signs of T cell exhaustion and heterogeneous expression levels of PD-1. Unexpectedly, PD-1high CAR-T cells outperformed PD-1low CAR-T cells in multiple T cell functions both in vitro and in vivo. Despite the achievement of superior persistence at the tumor site in vivo, adoptive transfer of PD-1high CAR-T cells alone failed to control tumor growth. Instead, a PD-1 blockade combination therapy significantly delayed tumor progression in mice infused with PD-1high CAR-T cells. Therefore, our data demonstrate that robust T cell activation during the ex vivo CAR-T cell manufacturing process generates a PD-1high CAR-T cell subset with improved persistence and enhanced anti-cancer functions. However, these cells may be vulnerable to the immunosuppressive microenvironment and require combination with PD-1 inhibition to maximize therapeutic functions in solid tumors.